2012
DOI: 10.1002/jemt.22013
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow cells of swine: Collection and separation

Abstract: Bone marrow is a source of stem cells for greater and easier access, which is widely studied as a provider of hematopoietic and mesenchymal cells for various purposes, mainly therapeutic by the advances in research involving cell therapy. The swine is an animal species commonly used in the pursuit of development of experimental models. Thus, this study aimed to standardize protocol for collection and separation of bone marrow in swines, since this species is widely used as experimental models for various disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
1
8
1
Order By: Relevance
“…As described by Samoto et al (2009) in the separation of bone marrow of dogs, the lipid accumulation was not detected, a fact recorded in swine's by Branco et al (2012); however, despite the liquid consistency of the material, we could notice the formation of small cell aggregates, independent of the use of anticoagulant at the time of collection, this fact was also observed by Alves et al (2009) when they performed extraction of bone marrow from horses sternum. The authors also reported the presence of spicules in the samples, as well as gelatinous consistency of all the material, which was not observed in our study.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…As described by Samoto et al (2009) in the separation of bone marrow of dogs, the lipid accumulation was not detected, a fact recorded in swine's by Branco et al (2012); however, despite the liquid consistency of the material, we could notice the formation of small cell aggregates, independent of the use of anticoagulant at the time of collection, this fact was also observed by Alves et al (2009) when they performed extraction of bone marrow from horses sternum. The authors also reported the presence of spicules in the samples, as well as gelatinous consistency of all the material, which was not observed in our study.…”
Section: Discussionsupporting
confidence: 73%
“…Sutter (2007) pointed out that progenitor cells are concentrated in first few millilitres of blood marrow, leading us to use only 13 ml. The cell viability of bone marrow from C. aethiops, reached an average of 97% after exclusion of Trypan blue dye, being higher than that found by Perin et al (2003) in humans (96%), more expressive when compared with the findings of Alves et al (2009) in horses (86.9%), however, slightly lower than the findings of Branco et al (2012) in swine (98%).…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations